Model comparisons of the costs of reducing CO2 emissions - Weyant, John P.; Gaskins, Darius W. (American Economic Review, 1993)
The Energy Modeling Forum working group 12 specified 13 standardized scenarios reflecting a range of carbon emission-control levels, as well as sensitivities on key standardized inputs. These scenarios were ultimately implemented by 14 modeling teams employing a wide variety of technoeconomic models, although not every model could implement every scenario. In addition to these model comparisons, ten study groups were formed to analyze issues not being addressed by the 14 models and 13 scenarios. These groups used additional models and methods to analyze issues not addressed in the 13 original scenarios.